1990
DOI: 10.1029/jd095id13p22547
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric response to Ice Age conditions: Climatology near the Earth's surface

Abstract: We present a 6‐year simulation of the ice age atmosphere using the T21 Atmospheric General Circulation Model (AGCM) of the European Centre for Medium‐Range Weather Forecasts (ECMWF). The lower boundary conditions (18 kyr B.P.) were taken from CLIMAP Project Members (1981). The analysis is restricted to the surface climatology for two reasons: The surface fields are the test data derived from the geological record on land, and they define the upper boundary conditions for simulating the glacial ocean. Model res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(28 citation statements)
references
References 22 publications
(16 reference statements)
3
25
0
Order By: Relevance
“…Averaged over the globe, the LGM experiment cooling is 3.2 ЊC, with more intense cooling in the Northern Hemisphere (where there is also more land) than in the Southern Hemisphere, yielding a pronounced asymmetry about the Equator. Cooling of 3.2 ЊC is slightly less than found in some AGCM studies [16][17][18] , although it is similar to the amount found in others 37,38 . In the Northern Hemisphere maximum winter-mean cooling of 14.4 ЊC is found in the North Atlantic; this weakens to about 6.8 ЊC in the summer.…”
Section: Simulations Of the Lgm And The Present Daysupporting
confidence: 75%
See 1 more Smart Citation
“…Averaged over the globe, the LGM experiment cooling is 3.2 ЊC, with more intense cooling in the Northern Hemisphere (where there is also more land) than in the Southern Hemisphere, yielding a pronounced asymmetry about the Equator. Cooling of 3.2 ЊC is slightly less than found in some AGCM studies [16][17][18] , although it is similar to the amount found in others 37,38 . In the Northern Hemisphere maximum winter-mean cooling of 14.4 ЊC is found in the North Atlantic; this weakens to about 6.8 ЊC in the summer.…”
Section: Simulations Of the Lgm And The Present Daysupporting
confidence: 75%
“…In the first, ocean-only models have been used in which surface forcing consists of restoring temperature and salinity to LGM reconstructions with specified atmospheric general circulation model (AGCM) LGM surface wind stress fields [12][13][14] . The second class of studies involves the integration of AGCMs with either fixed SST or mixed-layer ocean models at the lower boundary [15][16][17][18][19] . Many of these modelling studies have found tropical SSTs consistent with CLIMAP, although this often (but not always; see, for example, ref.…”
mentioning
confidence: 99%
“…There is a large number of other model simulations of the LGM ocean based on a wide variety of OGCMs, which for example employ air temperature and freshwater flux from an atmospheric model (Lautenschlager and Herterich 1990;Bigg et al 1998), reconstructions of SST and SSS (Seidov et al 1996;Winguth et al 1999) or an energy balance model for the temperature boundary condition (Fieg and Gerdes 2001). Two coupled model studies were carried out with intermediate complexity models (Ganopolski et al 1998;Weaver et al 1998).…”
Section: Comparison To Climapmentioning
confidence: 99%
“…Hyde et al 1989) and AGCMs (e.g. Lautenschlager & Herterich 1990). 3 Models that asynchronously couple a climate model to one or several ice sheet models (Marsiat 1994).…”
Section: Cryospherementioning
confidence: 99%